Correlation between duration of Diabetes and Severity of Retinal Changes - Shafqat Ali Shah, Muhammad Bilal, Muhammad Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetic retinopathy (DR) is the most frequent microvascular complication of diabetes mellitus and a significant cause of avoidable blindness in the world. The long-term effects of hyperglycemia are chronic retinal microangiopathy, and the number of years is considered one of the strongest predictors of retinal structural damage and visual loss, especially in resource-deprived contexts. Purpose: To establish the relationship between type-2 diabetes mellitus duration and diabetic retinopathy severity in adult patients who visit a tertiary-care ophthalmological clinic. Methodology: It was a cross-sectional study conducted at department of Ophthalmology unit BKMC Mardan from June 2022 to December 2022. A sample of 120 patients who had confirmed diabetes mellitus type 2 was selected through a consecutive sampling. The demographic parameters and period of diabetes were noted. Dilated fundus examination was performed on all participants with the help of the slit-lamp biomicroscope with a 90-diopter lens. The grading of retinal changes was conducted in accordance with the Early Treatment Diabetic Retinopathy Study (ETDRS). The analysis of data was performed with the help of SPSS version 24. Chi-square test and Spearman correlation were used to test the association between duration of diabetes and the severity of retinopathy. A p-value of 0.05 or below was regarded as statistically significant. Results: The mean age of participants was 55.1 ± 9.2 years, with 68 (56.7%) males. Mean duration of diabetes was 10.2 ± 5.4 years. Diabetic retinopathy was present in 74 (61.7%) patients, including mild NPDR in 25.0%, moderate NPDR in 17.5%, severe NPDR in 10.8%, and proliferative DR in 8.4%. Retinopathy prevalence increased significantly with longer disease duration: 12.8% in ≤5 years, 54.3% in 6–10 years, and 88.6% in >10 years duration groups. A strong positive correlation was observed between duration of diabetes and retinopathy severity (r = 0.69; p < 0.001). Conclusion: Diabetes duration has a strong and statistically significant relationship with diabetic retinopathy severity, which emphasises the need to diagnose and conduct regular retina screening to avoid diabetic retinopathy complications with vision risks. Keywords: Diabetes, Retinopathy, Duration, Severity.